A resistant starch type rs3 containing added water insoluble solid microparticle seeds
Patent Information
- Application Number
- CN202611238937.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-16
- Publication Date
- 2026-10-27
AI Technical Summary
然而,气泡模板在粘稠淀粉体系中稳定性极差、工业化不可行;自晶种路线效率低下且已有在先技术公开;凝胶态物质路线会引入额外配料,破坏清洁标签属性,且凝胶剂在退火温度下呈半固态而非固体微粒形态,不属于本发明的保护对象——但该路线因配料不干净而丧失市场竞争力
(1)上位概念全覆盖:以“含有外加水不溶性固体微粒晶种”的上位概念撰写,所有添加了水不溶性固体微粒作为晶种的RS3型抗性淀粉产品均落入保护范围。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of modified starch technology, specifically relating to a high-melting-point RS3 type resistant starch product containing added food-grade water-insoluble solid microparticle seed crystals. Background Technology RS3 resistant starch is a heat-stable crystalline resistant starch formed by the ordered rearrangement of amylose molecules along the surface of heterogeneous nucleation seed crystals during annealing. Its core characteristic is a melting temperature ≥120℃. Heterogeneous nucleation seed crystals play a decisive role in the RS3 crystallization process—without a seed template, amylose molecules can only undergo disordered retrogradation through slow homogeneous nucleation, requiring annealing times of up to several hours. Furthermore, the resulting type B retrograded starch typically has a melting temperature below 100℃ and lacks high-temperature processing tolerance. Existing technologies have disclosed methods for using residual natural starch microcrystals in starch-containing raw materials as endogenous seed crystals, exogenously added proteins, added starch microcrystals, and lipid or small molecule crystals as heterogeneous nucleation seed crystals. However, the protection scope of the above methods is limited to organic seed crystals. Food-grade inorganic salt crystals (calcium carbonate, calcium sulfate, etc.) and mineral microparticles (talc, etc.) also have regular crystal surfaces, which can induce heterogeneous nucleation and ordered rearrangement of amylose molecules. Furthermore, these are common food additives, and competitors may circumvent this by using the guise of "nutritional fortification" or "anti-caking agents" to actually act as "seed crystals." In addition, three potential alternative routes exist in this field: one is to use bubbles or gas-liquid interfaces as nucleation templates; the second is to use temperature cycling to induce self-crystallization of amylose (self-seeding); and the third is to use gel-like substances (agar, carrageenan, etc.) as nucleation templates. However, bubble templates have extremely poor stability in viscous starch systems and are not industrially feasible; the self-seeding route is inefficient and already has prior art; the gel-like substance route introduces additional ingredients, compromising clean label properties, and the gelling agent is in a semi-solid rather than solid particulate form at annealing temperature, which is not the subject of this invention—although this route loses market competitiveness due to unclean ingredients. Therefore, none of the above three alternative routes constitute a substantial threat to this invention. This invention specifically blocks the bypass routes of inorganic salts and dietary fiber seeds, and for the first time takes RS3 type resistant starch product containing added water-insoluble solid microparticle seeds as the protected object, defining the product characteristics by the physical properties of the overarching concept of "water-insoluble solid microparticles". Summary of the Invention Purpose of the invention This invention provides an RS3 type resistant starch product containing added water-insoluble solid microparticle seed crystals. By writing a higher-level concept, the product characteristics are defined by the physical properties of the solid microparticles rather than specific chemical names, thus blocking the path for competitors to circumvent the core patent and produce similar products using inorganic salts or dietary fiber seed crystals. Technical solution This RS3 resistant starch is based on starch-containing raw materials and contains added food-grade water-insoluble solid microparticles as heterogeneous nucleation seed crystals. The protein content of the starch-containing raw materials is ≤10% and does not contain gluten. The melting point or decomposition temperature of the solid microparticles is ≥120℃, the particle size is 10nm-50μm, and the addition amount is 0.1%-10% of the dry weight of the starch-containing raw materials. The surface of the solid microparticles is coated with an RS3 crystalline layer, with a coating coverage of ≥80% and a thickness of 50-500nm. The product simultaneously meets the following requirements: RS3 content ≥7%, RS3 melting temperature ≥120℃, and GI value ≤65. The RS3 resistant starch is prepared by a purely physical annealing process with an annealing temperature of 50-70℃ and an annealing time of 8-20 minutes. During the annealing process, the amylose molecules adhere to the surface of the solid particles in an orderly manner and rearrange in the crystal lattice to form a high-melting-point RS3 crystalline layer. Core Mechanism Water-insoluble solid particles (including inorganic salt crystals and insoluble dietary fiber microcrystals) play a core role as heterogeneous nucleation seeds in the annealing system. The solid particles have regular crystal surfaces or ordered molecular arrangements. When the starch-containing raw material absorbs water and swells during the conditioning stage and partially gelatinizes at the annealing temperature, the released amylose molecules migrate to the surface of the solid particles under the drive of thermal motion. The ordered atomic or molecular arrangement on the surface of solid particles provides an energy-optimal template for the attachment of amylose molecules. Amylose molecules align themselves orderly along the particle surface through hydrogen bonds and van der Waals forces, forming initial crystal nuclei. Under sustained annealing temperature, more amylose molecules continue to diffuse to and attach orderly to the surface of the crystal nuclei, gradually growing into a dense RS3 crystalline layer. Under a scanning electron microscope, this crystalline layer appears as a continuous, dense coating on the surface of the solid particles, with a coverage of ≥80% and a thickness typically ranging from 50 to 500 nm. Compared to prior art organic seed crystals (natural starch microcrystals, protein, and lipid crystals), inorganic salt crystals (such as calcium carbonate and calcium sulfate) have higher thermal stability and more regular crystal lattice structures, and do not soften or decompose at annealing temperatures of 50-70℃. Insoluble dietary fiber microcrystals (such as microcrystalline cellulose) have abundant surface hydroxyl groups and an ordered molecular arrangement, and can also serve as highly efficient heterogeneous nucleation templates. The essential differences between this invention and prior organic seed technology are: (1) different objects of protection - prior technology protects methods or processes, while this invention protects the product itself containing added seed crystals; (2) different types of seed crystals - prior technology is limited to organic seed crystals, while this invention extends to inorganic salt crystals and insoluble dietary fiber microcrystals; (3) different writing methods - prior technology is limited to the specific chemical names of subordinate concepts, while this invention is limited to the physical properties of subordinate concepts. Beneficial effects (1) Full coverage of the superordinate concept: The superordinate concept is written as “containing added water-insoluble solid microparticle seed crystals”, and all RS3 type resistant starch products that have added water-insoluble solid microparticles as seed crystals fall within the scope of protection. (2) Blocking detour routes: The inorganic crystal seeds (calcium carbonate, calcium sulfate, talc, etc.) and dietary fiber microcrystalline seeds (microcrystalline cellulose) that competitors may use are all covered at the product level at one time. (3) Pure physical process: The ingredient list does not contain chemical modifiers and exogenous enzyme preparations, and meets the clean label standards. (4) Strong operability of rights protection: The solid particles in the product and the RS3 crystal layer attached to its surface (coating coverage ≥80%, thickness 50-500nm) can be directly observed and quantitatively measured by scanning electron microscope (SEM), combined with energy dispersive spectroscopy (EDX) or X-ray diffraction (XRD) for qualitative and quantitative detection, without the need to prove the manufacturing method. Detailed Implementation The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to these specific examples. All parts mentioned in the embodiments are parts by mass, and all percentages are percentages by mass. Example 1 (Calcium carbonate microparticles + corn starch) Take 20g of food-grade calcium carbonate micron powder conforming to GB 1886.214 (average particle size 5μm, purity ≥98%) and mix it with 1000g of corn starch (amylose content approximately 27%, protein content 0.3%) in a high-speed mixer at 200rpm for 10 minutes. Add water to adjust the moisture content to 28% and maintain the temperature at 48℃, continuing to stir until the moisture is evenly distributed. The conditioned mixture was fed into a constant temperature and humidity annealing apparatus and annealed at 60℃ and 85% relative humidity for 12 minutes. After annealing, a gradient slow cooling method was used for cooling and shaping: the first stage cooled from 60℃ to 42℃ at a rate of 3.5℃ / min, and the second stage cooled from 42℃ to 33℃ at a rate of 1.5℃ / min. Subsequently, it was dried at a low temperature of 45℃ until the moisture content was 12.0%, and then passed through a 100-mesh sieve to obtain the product. Results of three parallel tests (n=3): RS3 resistant starch content was 8.2%±0.5% (≥7%, determined by AOAC 2002.02 standard method); RS3 resistant starch melting temperature was 124±1℃ (≥120℃, determined by DSC, heating rate 10℃ / min, nitrogen atmosphere, sample amount 3-5mg, temperature range 30-180℃, recording the peak temperature of the endothermic peak); GI value was 62±2 (≤65). Scanning electron microscopy (SEM) showed that the surface of calcium carbonate particles was coated with a continuous and dense RS3 crystalline layer, with a coverage of about 92% and a thickness of about 80-120nm. Energy dispersive spectroscopy (EDX) confirmed that the carbon and oxygen distribution in the coating layer was in the same region as the calcium distribution in calcium carbonate, confirming the orderly growth of the RS3 crystalline layer on the surface of calcium carbonate particles. The ingredient list of the resulting product contains only corn starch and calcium carbonate, and contains no chemical modifiers or exogenous enzyme preparations. Example 2 (microcrystalline cellulose + wheat starch) Take 15g of microcrystalline cellulose (average particle size 20μm, degree of polymerization approximately 220) and mix it evenly with 1000g of wheat starch (amylose content approximately 25%, protein content 0.4%). Add water to adjust the moisture content to 25% and maintain the temperature at 48℃. The conditioned mixture was fed into a constant temperature and humidity annealing apparatus and annealed at 58℃ and 85% relative humidity for 14 minutes. After annealing, a gradient slow cooling method was used for cooling and shaping: the first stage cooled from 58℃ to 40℃ at a rate of 3.5℃ / min, and the second stage cooled from 40℃ to 33℃ at a rate of 1.5℃ / min. Subsequently, it was dried at a low temperature of 42℃ until the moisture content was 12.0%, and then passed through a 100-mesh sieve to obtain the product. Results of three parallel tests (n=3): RS3 resistant starch content was 7.8%±0.4% (≥7%), RS3 resistant starch melting temperature was 122±1℃ (≥120℃), and GI value was 63±2 (≤65). SEM images showed that the surface of microcrystalline cellulose was coated with an RS3 crystalline layer, with a coverage of about 85% and a thickness of about 60-100 nm, confirming the heterogeneous nucleation function of dietary fiber microcrystals. The ingredient list of the resulting product contains only wheat starch and microcrystalline cellulose, and contains no chemical modifiers or exogenous enzyme preparations. Example 3 (Talc powder + Rice starch) Take 10g of food-grade talc powder conforming to GB 1886.246 (average particle size 3μm, purity ≥95%) and mix it evenly with 1000g of rice starch (amylose content approximately 20%, protein content 0.5%). Add water to adjust the moisture content to 30% and maintain the temperature at 48℃. The conditioned mixture was fed into a constant temperature and humidity annealing apparatus and annealed at 62℃ and 88% relative humidity for 10 minutes. After annealing, it was rapidly cooled to below 25℃ within 90 seconds using a fluidized bed with -3℃ cold air to lock the RS3 lattice structure. Subsequently, it was dried at 45℃ until the moisture content was 11.5%, and then passed through a 100-mesh sieve to obtain the product. The results of three parallel tests (n=3) showed that the content of RS3 resistant starch was 7.5%±0.4% (≥7%), the melting temperature of RS3 resistant starch was 121±1℃ (≥120℃), and the GI value was 64±2 (≤65). XRD patterns showed that the characteristic diffraction peaks of talc powder and the B-type crystallization peaks of RS3 could be clearly distinguished, confirming the presence of both added seed crystals and in-situ generated RS3 crystals in the product. The ingredient list of the resulting product contains only rice starch and talc, and contains no chemical modifiers or exogenous enzyme preparations. Example 4 (Calcium sulfate + corn starch) Take 25g of food-grade calcium sulfate micronized powder conforming to GB 1886.6 (average particle size 8μm, purity ≥98%) and mix it evenly with 1000g of corn starch. Add water to adjust the moisture content to 28% and the temperature to 48℃. Anneal at 62℃ and 85% relative humidity for 13 minutes. Gradually cool to 33℃ and dry at 45℃ until the moisture content is 12.0%. Pass through a 100-mesh sieve to obtain the product. The results of three parallel tests (n=3) showed that the content of RS3 resistant starch was 7.9%±0.4% (≥7%), the melting temperature of RS3 resistant starch was 123±1℃ (≥120℃), and the GI value was 62±2 (≤65). An RS3 crystalline layer was also attached to the surface of the calcium sulfate microparticles, with a coating coverage of approximately 88%, confirming the versatility of the inorganic salt seed crystals. The ingredient list of the resulting product contains only corn starch and calcium sulfate, and contains no chemical modifiers or exogenous enzyme preparations. Example 5 (Mixed Seed Crystals – Calcium Carbonate + Microcrystalline Cellulose) Mix 10g of food-grade calcium carbonate micron powder (average particle size 5μm) with 8g of microcrystalline cellulose (average particle size 20μm), then add to 1000g of corn starch. Mix thoroughly in a high-speed mixer at 200rpm for 12 minutes. Add water to adjust the moisture content to 28% and heat to 48℃. Anneal under the same conditions as in Example 1 (60℃, 85%RH, 12 minutes), then gradually cool to 33℃ and dry at 45℃ until the moisture content reaches 12.0%. Pass through a 100-mesh sieve to obtain the product. Results of three parallel tests (n=3): RS3 resistant starch content 8.5%±0.5% (≥7%), RS3 resistant starch melting temperature 125±1℃ (≥120℃), GI value 61±2 (≤65). The mixed use of inorganic salt crystals and dietary fiber microcrystals produced a synergistic enhancement effect—two seed crystals of different sizes and surface chemistry provided diverse nucleation sites for amylose molecules, and the RS3 formation efficiency was slightly better than that of a single seed crystal (8.2% in Example 1). SEM-EDX analysis showed that both calcium carbonate microparticles and microcrystalline cellulose were coated with RS3 crystal layers, with a coating coverage of ≥85%, confirming the synergistic nucleation effect of the mixed seed crystals. The ingredient list of the resulting product contains only corn starch, calcium carbonate, and microcrystalline cellulose, and contains no chemical modifiers or exogenous enzyme preparations. Comparative Example 1 (no added solid particles - refined starch) Omit the calcium carbonate micro powder in Example 1, and keep the other conditions unchanged: 1000g of corn starch (refined starch, which has been thoroughly washed with water to remove most of the natural residual microcrystals, and no visible natural starch crystal melting peaks were observed by DSC) was added to water to adjust the moisture content to 28%, annealed at 60°C and 85% relative humidity for 12 minutes, gradually cooled to 33°C, and dried at 45°C to 12.0% moisture content. The results of three parallel tests (n=3) showed that the content of RS3 resistant starch was only 4.5%±0.3% (<7%), the melting temperature of RS3 resistant starch was 112±2℃ (<120℃), and the GI value was 72±3 (>65). This demonstrates that without the addition of external solid microparticle seed crystals, a single annealing process cannot generate sufficient amounts of high-melting-point RS3 resistant starch under the same conditions; therefore, the addition of seed crystals is a necessary condition for the product to meet the standards. Comparative Example 2 (Adding soluble inorganic salts to replace insoluble microparticles) The calcium carbonate powder in Example 1 was replaced with an equal amount of sodium chloride (soluble in water and completely ionized in aqueous solution), while all other conditions remained unchanged. The results of three parallel tests (n=3) showed that the content of RS3 resistant starch was 4.8% ± 0.4% (<7%), and the melting temperature of RS3 resistant starch was 108 ± 2℃ (<120℃). Sodium chloride completely dissolved in water during the conditioning process and could not exist as solid particles at the annealing temperature, thus losing its heterogeneous nucleation seed function. This proves that solid particles must remain insoluble in the solid state at the annealing temperature to exert their heterogeneous nucleation effect. Comparative Example 3 (Solid particles with diameters outside the acceptable range) The calcium carbonate micro powder in Example 1 was replaced with an equal amount of food-grade calcium carbonate coarse powder (average particle size 200 μm, exceeding the upper limit of the 10 nm-50 μm range), with all other conditions remaining unchanged. Results of three parallel tests (n=3): RS3 resistant starch content was 5.2%±0.4% (<7%), and the melting temperature of RS3 resistant starch was 110±2℃ (<120℃). Larger solid particles have a smaller specific surface area, resulting in insufficient heterogeneous nucleation sites per unit mass. This makes it difficult for gelatinized amylose molecules to adhere uniformly and rearrange orderly on the particle surface, significantly reducing RS3 formation efficiency. This demonstrates that the particle size of the solid particles must be controlled within the range of 10nm-50μm to effectively perform heterogeneous nucleation. Comparative Example 4 (annealing temperature exceeds the effective range) The annealing temperature in Example 1 was changed to 85°C, while the other conditions remained unchanged. Results of three parallel tests (n=3): RS3 resistant starch content was 4.2%±0.4% (<7%), and the melting temperature of RS3 resistant starch was 105±2℃ (<120℃). At 85℃, although the calcium carbonate microparticles did not melt, the high temperature caused excessive gelatinization of the starch granules, leading to the collapse of the natural microcrystalline template. Even with added seed crystals, the surface could not effectively induce ordered rearrangement, resulting in substandard products. This demonstrates that the annealing temperature must be controlled within the range of 50-70℃. Comparative Example 5 (Insufficient amount of solid particles added) The amount of calcium carbonate powder added in Example 1 was reduced to 0.5g (0.05% of the dry weight of starch, below the lower limit of 0.1%), while the other conditions remained unchanged. The results of three parallel tests (n=3) showed that the content of RS3 resistant starch was 5.5% ± 0.4% (<7%), and the melting temperature of RS3 resistant starch was 115 ± 2℃ (<120℃). When the addition amount was too low, the number of solid particles was insufficient to provide enough heterogeneous nucleation sites, resulting in limited RS3 formation efficiency. This demonstrates that the addition amount of solid particles needs to be ≥0.1% to effectively exert the seed crystal function. Comparative Example 6 (Restricted Applicability of Gluten Protein Raw Materials) In Example 2, the wheat starch was replaced with high-gluten wheat flour (protein content 14.2%, wet gluten content 33%), and 15g of microcrystalline cellulose was added, with all other conditions remaining unchanged. The annealing temperature was adjusted to 51℃ (the annealing temperature of wheat flour must be below the critical temperature for thermal denaturation of gluten protein). The results of three parallel tests (n=3) showed that the RS3 resistant starch content was 7.0%±0.4% (≥7%), the RS3 resistant starch melting temperature was 121±1℃ (≥120℃), and the GI value was 64±2 (≤65). However, the wet gluten retention rate was only 52% (<85%), and the fiber-drawing performance was lost. During the annealing process, the gluten network of gluten-containing raw materials is temperature-sensitive. Although the added solid particles can promote RS3 formation, they cannot compensate for the thermal denaturation damage of gluten proteins. This demonstrates that the added seed crystal product of this invention is suitable for starch-containing raw materials with a protein content ≤10% and no gluten proteins. Comparative Example 7 (Excessive Addition of Solid Particles) The amount of calcium carbonate powder added in Example 1 was increased to 120g (accounting for 12% of the dry weight of starch, exceeding the upper limit of the range of 0.1%-10%), while the other conditions remained unchanged. The results of three parallel tests (n=3) showed that the content of RS3 resistant starch was 5.0% ± 0.4% (<7%), and the melting temperature of RS3 resistant starch was 109 ± 2℃ (<120℃). When the addition amount was too high, excessive solid particles formed a physical barrier in the annealing system, hindering the contact and orderly arrangement between amylose molecules, and simultaneously diluting the starch concentration, thus inhibiting the efficient formation of the RS3 lattice. This proves that the addition amount of solid particles should be ≤10%; products exceeding this limit are substandard. Comparative Example 8 (Head-to-head comparison of inorganic salt seed crystals vs. organic seed crystals) To demonstrate the high level of creativity of inorganic salt seed crystals, a head-to-head comparative experiment was conducted: Experimental Group A (this patent): Corn starch + calcium carbonate 5μm (2%), annealed at 60℃ for 12 minutes, RS3 content 8.2%±0.5%, RS3 melting temperature 124±1℃ Experimental Group B (Pre-existing organic seed crystals – added starch microcrystals): Corn starch + added starch microcrystals (2%, average particle size 5μm), annealed at 60℃ for 12 minutes, RS3 content 7.6%±0.4%, RS3 melting temperature 121±1℃ Experimental group C (pre-existing organic seed crystals – lipid crystals): corn starch + glyceryl monostearate crystals (2%), annealed at 60℃ for 12 minutes, RS3 content 7.2%±0.5%, RS3 melting temperature 120±1℃ Control group D (no added seed crystals): Corn starch, annealed at 60℃ for 12 minutes, RS3 content 4.5%±0.3%, RS3 melting temperature 112±2℃ Calcium carbonate seeds outperformed organic seeds (7.6% and 121℃, 7.2% and 120℃) in both RS3 content (8.2%) and melting temperature (124℃). Combined with the secondary processing tolerance data of Comparative Example 9, inorganic salt seeds exhibited high-temperature processing stability that organic seeds could not achieve, resulting in an unexpected technical effect. Comparative Example 9 (RS Retention Rate After Secondary Processing – The Real Advantage of Inorganic Salt Seeds) To demonstrate the real advantages of inorganic salt seed crystals under high-temperature processing conditions, the products from each seed crystal group in Example 1 and Comparative Example 8 were subjected to steam cooking at 100°C for 20 minutes (simulating baking / cooking secondary processing), and the RS3 retention rate after cooking was measured. Experimental Group A (calcium carbonate seed crystals): RS3 content was 8.2% before cooking and 7.0% after cooking, with a retention rate of 85.4%. Experimental group B (starch microcrystal seed): RS3 content was 7.6% before cooking and 3.8% after cooking, with a retention rate of 50.0%. Experimental group C (lipid seed crystals): RS3 content was 7.2% before cooking and 3.0% after cooking, with a retention rate of 41.7%. The RS3 retention rate of the calcium carbonate seed group (85.4%) was significantly higher than that of the starch microcrystal group (50.0%) and the lipid crystal group (41.7%), and the difference was statistically significant (p<0.01). The mechanism is as follows: Under excessive water cooking conditions, the gelatinization temperature of the starch crystallization zone is lower than the dry DSC measurement value. The RS3 crystalline layer, which is not supported by seed crystals, partially defolds under hydrothermal action. Meanwhile, the calcium carbonate microparticles maintain a solid structure at the cooking temperature, with a melting point of approximately 800℃, much higher than the cooking temperature. This forms a physical confinement on the surrounding RS3 crystalline layer, inhibiting excessive expansion of starch granules and defolding of the crystalline zone, thereby significantly improving the secondary processing retention rate of RS3. Starch microcrystals and lipid crystals soften or melt at 100℃, losing their seed crystal support function, and the RS3 crystalline layer subsequently disintegrates. This "secondary processing tolerance" is an unexpected technical effect that distinguishes inorganic salt seed crystals from organic seed crystals, constituting a substantial inventive contribution of this invention. Detection methods RS3 resistant starch content: determined using the AOAC 2002.02 standard method. The melting temperature of RS3 resistant starch was determined using differential scanning calorimetry (DSC). The heating rate was 10℃ / min, the atmosphere was nitrogen, the sample amount was 3-5 mg, the temperature range was 30-180℃, and the peak temperature of the endothermic peak was recorded. GI value: determined by in vitro enzymatic hydrolysis estimation method or ISO 26642:2010 standard method. Solid particle size: determined using a laser particle size analyzer or scanning electron microscope (SEM). SEM samples were sputter-coated with gold, accelerated at a voltage of 5-10 kV, and at least 100 particles were randomly selected for size measurement, with the average value taken. Observation of solid particle dispersion uniformity and surface RS3 crystalline layer: Qualitative and quantitative detection was performed using SEM combined with energy dispersive spectroscopy (EDX) or X-ray diffraction (XRD). The RS3 crystalline layer exhibits a continuous and dense coating morphology, with a coating coverage of ≥80% and a thickness of 50-500 nm. Coverage measurement method: At least 10 fields of view (magnification 10000-50000x) were randomly selected from the SEM images. Image analysis software (such as ImageJ) was used to calculate the percentage of the particle surface covered by the crystalline layer to the total particle surface area, and the average value was taken. XRD scanning conditions: Cu target Kα radiation, scanning range 2θ=5°-40°, scanning speed 2° / min, step size 0.02°. Moisture content: determined by the first method (direct drying method) of GB 5009.3-2016. Protein content: determined by the Kjeldahl method (GB 5009.5). Wet gluten content: determined by the gluten analyzer method or hand washing method according to GB / T 14608. Industrial applications The product of this invention can be produced on existing continuous grain conditioning-annealing-cooling-drying production lines, requiring only the addition of a mixing process between solid particles and starch raw materials before conditioning. The core equipment includes a high-speed mixer, a twin-shaft differential atomizing continuous conditioning tank, a closed mesh belt continuous annealing tower with ±0.5℃ temperature control accuracy across the entire range, a multi-stage air-cooled conveyor belt or fluidized bed quenching system, and low-temperature airflow drying equipment. The RS3 content, RS3 melting temperature, GI value, uniformity of solid particle dispersion, and RS3 crystallization layer coating status of the product must be included in the product's factory inspection standards. The coating coverage and thickness can be confirmed through random sampling using SEM-EDX. The ingredient list contains only starch raw materials and water-insoluble solid particles, and does not contain chemical modifiers or exogenous enzyme preparations, meeting clean label standards. This product can be directly supplied to low-GI food processing plants and functional food ingredient manufacturers. Downstream customers can choose different types of water-insoluble solid microparticle seed products according to specific application scenarios.
Claims
1. A high-melting-point RS3 type resistant starch containing added water-insoluble solid microparticle seeds, characterized in that, The RS3 resistant starch is based on starch-containing raw materials and contains added food-grade water-insoluble solid microparticles as heterogeneous nucleation seeds. The protein content of the starch-containing raw materials is ≤10% and does not contain gluten protein. The melting point or decomposition temperature of the solid microparticles is ≥120℃. The surface of the solid microparticles is coated with an RS3 crystalline layer with a coverage rate ≥80% and a thickness of 50-500nm. It also meets the following characteristics: RS3 type resistant starch content ≥7% (determined according to AOAC 2002.02 standard method); RS3 type resistant starch melting temperature ≥120℃ (determined by differential scanning calorimetry, heating rate 10℃ / min, nitrogen atmosphere, sample amount 3-5mg, temperature range 30-180℃, record the peak temperature of the endothermic peak). GI value ≤ 65; Furthermore, the ingredient list does not contain chemical modifiers or exogenous enzyme preparations, and the amount of solid microparticles added is 0.1%-10% of the dry weight of the starch-containing raw material.
2. The RS3 type resistant starch according to claim 1, characterized in that, The particle size of the solid particles is 10 nm-50 μm.
3. The RS3 type resistant starch according to claim 1, characterized in that, The solid particles are any one or more of inorganic salt crystals or insoluble dietary fiber microcrystals.
4. The RS3 type resistant starch according to claim 3, characterized in that, The inorganic salt crystals are selected from any one or more of food-grade calcium carbonate, calcium sulfate, calcium phosphate, and talc.
5. The RS3 type resistant starch according to claim 3, characterized in that, The insoluble dietary fiber microcrystals are microcrystalline cellulose.
6. The RS3 type resistant starch according to claim 1, characterized in that, The amount of the solid particles added is 0.5%-5% of the dry weight of the starch-containing raw material.
7. The RS3 type resistant starch according to claim 1, characterized in that, The RS3 resistant starch has a melting temperature ≥125℃, a GI value ≤60, and a resistant starch content ≥8%.
8. A method for preparing the RS3 type resistant starch according to any one of claims 1-7, characterized in that, The process includes the following steps: mixing starch-containing raw materials with a protein content ≤10% and no gluten protein with food-grade water-insoluble solid particles, adding water to adjust the moisture content to 20%-35%, controlling the temperature at 45-50℃, and annealing at 50-70℃ and 80%-95% relative humidity for 8-20 minutes to allow the amylose molecules to attach orderly along the surface of the solid particles and rearrange the crystal lattice to form an RS3 crystalline layer. Then, cooling and setting the temperature to below 35℃, and drying at a temperature not exceeding 60℃ to a moisture content of below 13%.
9. The use of the RS3 type resistant starch according to any one of claims 1-7 in the preparation of low-GI foods.